The efficacy of open transanal drainage tube against anastomotic leakage in left-sided colorectal cancer surgery: a propensity score matching study - Gen Tsujio; Tatsunari Fukuoka; Atsushi Sugimoto; Ken Yonemitsu; Yuki Seki; Hiroaki Kasashima; Yuichiro Miki; Mami Yoshii; Tatsuro Tamura; Masatsune Shibutani; Takahiro Toyokawa; Shigeru Lee; et al. (BMC Surgery)
Abstract Background/Aim The effectiveness of a transanal drainage tube (TAT) for the prevention of anastomotic leakage after double stapling technique (DST) anastomosis in colorectal cancer has been reported. Previously, TATs had been placed and connected to drainage bags. It was considered that a higher decompression effect could be expected by inserting an open-type TAT, without connection to a drainage bag. In this study, the relation between anastomotic leakage and the application of this type of TAT in left-sided colorectal cancer surgery was investigated, using propensity score matching (PSM). Materials and methods From January 2016 to July 2023, 233 consecutive patients underwent radical surgery for sigmoid colon and rectal cancers and reconstruction using DST at Osaka Metropolitan University Hospital. Patients were divided into two groups: those who had a closed TAT inserted (CLOSED group), and those who had an open TAT inserted (OPEN group). Results Overall, open TATs were inserted in 43 patients, and closed TATs were inserted in 190 patients. PSM was performed between the OPEN and CLOSED groups on the basis of the following 13 factors: age, sex, BMI, diabetes mellitus (DM), smoking history, modified Glasgow prognostic score (mGPS), ASA-PS, location of distal tumor edge, operative procedure, surgical approach, operative time, intraoperative blood loss, and pathological stage. The multivariate analysis of significant factors identified a BMI of 25 or more, a location of distal edge on middle to lower rectum, and a closed TAT, as independent risk factors for anastomotic leakage (HR: 8.72; p = 0.038, HR: 10.06; p = 0.034 and HR: 17.43; p = 0.033). Conclusion An open TAT may be effective in preventing anastomotic leakage in left-sided colorectal cancer surgery.